Design and performance evaluation of the six-row side deep fertilizer applicator for paddy fields - Bangura, Kemoh; Wu, Shuanglong; Tang, Zhenyu; Feng, Xiao; Hu, Renjun; Cai, Yinghu; Zhou, Yuhao; Liang, Zhanpeng; Zeng, Zhiwei; Bangura, Abdulai; et al. (International Journal of Agricultural and Biological Engineering, 2024)
Deep application of chemical fertilizer is an alternative method to improve the fertilizer utilization efficiency of directly seeded and transplanted rice and minimize the adverse effects of fertilizer on the environment. Different fertilization machines have been introduced for fertilizer deep placement. However, machines for this purpose have not been widely accepted due to the problem of inconsistent performance in applications. In response to this problem, this study developed a six-row deep fertilizer applicator with an improved discharge device. The structural design of the discharge device was optimized, and field performance experiments were conducted on the entire machine. First, a single row operation model of the fertilizer applicator was established based on the Discrete Element Method (DEM). Three spiral grooved wheel speeds were used to test the uniformity and accuracy of fertilization. The optimization test results showed that the spiral grooved wheel has good fertilizer discharge effect at a speed of 40 r/min, a groove radius of 6 mm, a grooved wheel working length of 50 mm, and a grooved wheel spiral angle of 45°. The coefficient of variation of fertilizer application uniformity under these parameter settings was 6.30%. Field experiments were conducted to test the machine’s performance under static and dynamic conditions. The static test results showed that the consistency and stability variations of fertilization in each row were less than 5%. When the expected fertilization rates were 150, 225, 300, and 375 kg/hm2, the fertilization accuracy of the six-row fertilization machine was 95.5%, and the overall deviation from the actual fertilization rates was less than 5%. The study provides a new tool for the advancement of rice fertilization technology and lays a research foundation for the development of efficient and precise rice fertilization machinery. Key words: deep fertilization device, structural design, DEM simulation, field experiment DOI: 10.25165/j.ijabe.20241706.8598 Citation: Bangura K, Wu S L, Tang Z Y, Feng X, Hu R J, Cai Y H, et al. Design and performance evaluation of the six-rowside deep fertilizer applicator for paddy fields. Int J Agric & Biol Eng, 2024; 17(6): 166–175.